Nicotine Causes Mitochondrial Dynamics Imbalance and Apoptosis Through ROS Mediated Mitophagy Impairment in Cardiomyocytes - Meng, Ting-ting; Wang, Wei; Meng, Fan-liang; Wang, Shu-ya; Wu, Hui-hui; Chen, Jia-min; Zheng, Yan; Wang, Guang-xin; Zhang, Mao-xiu; Li, Ying; Su, Guo-hai (Frontiers in Physiology, 2021)
Nicotine contained in traditional cigarettes, hookahs and e-cigarettes is an important risk factor for cardiovascular disease. Our previous study showed that macroautophagic flux impairment occurred under nicotine stimulation. However, whether nicotine influences mitochondrial dynamics in neonatal rat ventricular myocytes (NRVMs) is unclear. The purpose of this study was to explore the effects and potential mechanism of nicotine on mitophagy, mitochondrial dynamics, apoptosis and the relationship between these processes in NRVMs. Our results showed that nicotine exposure increased mitochondria- -derived superoxide production, decreased mitochondrial membrane potential, and impaired PINK1/Parkin-mediated mitophagic flux in NRVMs. Interestingly, nicotine significantly promoted dynamin-related protein 1 (Drp1)-mediated mitochondrial fission and suppressed mitofusin (MFN)-mediated fusion, which was also observed in the bafilomycin A1-treated group. These results suggest that mitophagic flux impairment may contribute to Drp-1-mediated mitochondrial fission. Finally, nicotine caused excessive mitochondrial fission and contributed to apoptosis, which could alleviate be alleviated by mdivi-1, , an inhibitor of Drp1. In addition to CTSB, as we previously reported, the enzyme activity of cathepsin L (CTSL) was also decreased in lysosomes after stimulation with nicotine, which may be the main cause of the hindered mitophagic flux induced by nicotine in NRVMs. Pretreatment with Torin 1, which is an inhibitor of mTOR, activated CTSL and ameliorated nicotine-induced mTOR activation and mitophagy impairment, decreased mitochondria-derived superoxide production, and blunted mitochondrial fission and apoptosis. Pretreatment with the ROS scavenger N-acetyl-cysteine (NAC) or inhibitors of p38 and JNK, which could also alleviate mitophagy impairment, exhibited similar effects as Torin1 on mitochondria. Taken together, our study demonstrated that nicotine treatment may lead to an increase in Drp1-mediated mitochondrial fission by blocking mitophagic flux by weakening the enzyme activity of CTSL and activating the ROS/p38/JNK signalling pathway. Excessive mitochondrial fission induced by nicotine ultimately leads to apoptosis. Torin1 restored the decreased CTSL enzyme activity by removing excessive ROS and alleviated the effects of nicotine on mitophagic flux, mitochondrial dynamics and apoptosis. These results may provide new evidence on the relationship between mitophagic flux and mitochondrial dynamics and new perspectives on nicotine’s effects on mitochondrial dynamics in cardiomyocytes.